1994
DOI: 10.3354/meps103207
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and biological factors controlling the concentrations of trace elements (As, Cd, Cu, Hg, Se, Zn) in delpinids Globicephala melas from the North Atlantic Ocean

Abstract: Ecological and biological factors controlling the concentrations of trace elements (As, Cd, Cu, Hg, Se, Zn) in delphinids Globicephala melas from the North Atlantic Ocean 'CNRS URA 1356, Service d'Ecotoxicologie. Faculte de Pharmacie, 1 rue Gaston Veil, F-44035 Nantes Cedex, France 'CNRS-IFREMER, CREMA I'Houmeau B.P. 5, F-17137 l'Houmeau, France ABSTRACT: Trace elements (As. Cd, Cu, Hg, Se and Zn) were determined in liver and kidney of pilot whales Glob~cephala melas Traill, 1809 collected from 7 schools caugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(15 citation statements)
references
References 22 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…Four negative correlations were observed that corroborate findings in other studies: Cu/Hg, Cu/Cd, Zn/Se, and Zn/Hg (Agusa et al 2008; Caurant et al 1994; Roditi-Elasar et al 2003). The negative correlation between Cu and Cd could be indicative of a competitive protein binding interaction as the same metallothionein isoform involved in Cu regulation and homeostasis is responsible for Cd sequestration (Caurant et al 1994; Roditi-Elasar et al 2003).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Four negative correlations were observed that corroborate findings in other studies: Cu/Hg, Cu/Cd, Zn/Se, and Zn/Hg (Agusa et al 2008; Caurant et al 1994; Roditi-Elasar et al 2003). The negative correlation between Cu and Cd could be indicative of a competitive protein binding interaction as the same metallothionein isoform involved in Cu regulation and homeostasis is responsible for Cd sequestration (Caurant et al 1994; Roditi-Elasar et al 2003).…”
Section: Resultssupporting
confidence: 89%
“…The positive correlations between Cd/Hg and Cd/Se found are consistent with many other studies and are generally thought to be age-dependent. However, shared detoxification mechanisms could also contribute to these patterns (Agusa et al 2008; Caurant et al 1994; Monaci et al 1998; Seixas et al 2007). A strong positive Hg/Pb correlation was also observed, similar to that identified in striped dolphins ( Stenella coeruleoalba ) by Agusa et al (2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In birds, this ratio is almost never found [38,43,44], as in the present study, where a 1:5 ratio was found. This is possibly the reason why the correlation between Hg and Se found here is moderate, and not strong or very strong, as has been reported in several studies involving marine mammals [45-47], since this protection mechanism seems to be inherent to marine mammals [43]. Other studies involving aquatic birds have found a larger quantity of selenium relative to mercury, precluding the 1:1 molar ratio, as in the present study [42,44,48].…”
Section: Resultssupporting
confidence: 78%
“…12 The study of trace elements in marine mammals is in its infancy in Brazil where few studies documented their concentrations in the tissues of cetaceans species with coastal habits such as Sotalia guianensis, Pontoporia blainvillei and oceanic habits such as Stenella frontalis. 7,11,[13][14][15][16][17] Furthermore, extensive studies of As, Cd, Cu, Pb, Se and Ag concentrations in cetaceans have been carried out in Northern Hemisphere 5,8,10,12,[18][19][20][21][22][23][24][25][26][27][28][29][30] but relatively little is known about contaminant levels in Southern Hemisphere cetaceans. [31][32][33][34][35] Then, the present research adds new insight to and complements the existing studies.…”
Section: Introductionmentioning
confidence: 99%